Method for unloading rock mass around a mine working in case of using longwall system for inclined seams in Donbass - A. V. Remizov (Горные науки и технологии, 2016)
The issues of protection and maintenance of stopes in the zone affected by stoping are considered in the context of the mines of Almazno-Maryevsky mining region of Donbass. Mine studies of manifestation of rock pressure influence on the stope contour are reviewed. Modeling has been carried out for these mining and geological conditions. The analysis characterizing the effect of unloading void on the stope stability has been carried out. Strain-stress diagrams to demonstrate the effect of rock mass unloading in case of using longwall system for inclined coal seams have been built.